2011
DOI: 10.1016/j.pain.2011.01.054
|View full text |Cite
|
Sign up to set email alerts
|

Leptin enhances NMDA-induced spinal excitation in rats: A functional link between adipocytokine and neuropathic pain

Abstract: Recent studies have shown that leptin (an adipocytokine) played an important role in nociceptive behavior induced by nerve injury, but the cellular mechanism of this action remains unclear. Using the whole cell patch-clamp recording from rat’s spinal cord slices, we showed that superfusion of leptin onto spinal cord slices dose-dependently enhanced NMDA receptor-mediated currents in spinal cord lamina II neurons. At the cellular level, the effect of leptin on spinal NMDA-induced currents was mediated through t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
70
3

Year Published

2013
2013
2015
2015

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 67 publications
(80 citation statements)
references
References 66 publications
4
70
3
Order By: Relevance
“…The proinflammatory cytokine-like functions of leptin in OA [10,[44][45][46][47] could explain its role in peripheral sensitization. Second, animal models suggest an involvement of leptin in the pathogenesis of pain at the spinal level and a possible role in the development of neuropathic pain [28][29][30]. Our clinical results support these experimental findings in patients with lower limb OA.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…The proinflammatory cytokine-like functions of leptin in OA [10,[44][45][46][47] could explain its role in peripheral sensitization. Second, animal models suggest an involvement of leptin in the pathogenesis of pain at the spinal level and a possible role in the development of neuropathic pain [28][29][30]. Our clinical results support these experimental findings in patients with lower limb OA.…”
Section: Discussionsupporting
confidence: 81%
“…Leptin levels in peritoneal fluid correlated positively with pain severity in endometriosis patients [27]. Furthermore, recent studies in rodents [28][29][30] suggested that spinal leptin might be involved in the pathogenesis of neuropathic pain.…”
Section: Introductionmentioning
confidence: 97%
“…[1][2][3][4] Adiponectin (ADP), leptin (LEP), and resistin are 3 such adipokines. These adipokines modulate inflammation and endothelial function-processes that overlap with the proposed mechanisms of migraine pathophysiology.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, receptors for these adipokines are expressed in key structures implicated in migraine, including the hypothalamus and the cerebral microvasculature. [1][2][3][4] Previous studies have reported that interictal ADP levels are increased in those with migraine, and that ictal ADP levels decline with successful abortive treatment in women episodic migraineurs. [5][6][7] Studies evaluating interictal LEP levels in migraineurs have been inconclusive.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation